Lactic acid bacteria isolated from Kazakh traditional fermented milk products affect the fermentation characteristics and sensory qualities of yogurt. Issue 5 (19th April 2022) - Li, Hui; Gao, Jiaxing; Chen, Wenbo; Qian, Chengjing; Wang, Yong; Wang, Jing; Chen, Lishui
Abstract: Lactic acid bacteria (LAB) play a crucial role in the development of the taste, texture, and aroma of traditional fermented milk products. Five LABs from Kazakh traditionally prepared dairy products showed continuous subculture stability, as well as proper acidification and coagulation ability. They were identified as Pediococcus pentosaceus (1–5, 1–7), Enterococcus faecium (1–19), and Lactobacillus plantarum (1–12, 1–15). Their coagulation time and acidity values ranged from 5.97 to 12.78 h and 76.47 to 89.39°T. Yogurts prepared with L. plantarum were more condensed and textural integrity than those with P. pentosaceus and E. faecium . Determination of the volatile compound profiles suggested a higher diversity of volatile compounds than the control. The sensory evaluation presented positive overall sensory quality scores for the yogurts prepared with 1–12 and 1–15. The results provide additional information regarding the contributions of native LABs to the unique flavor and sensory qualities of traditionally prepared milk products. They may help to select starters or adjunct starters for developing distinctive, traditional nomadic fermented milk to satisfy consumer demand and increase market acceptability. Abstract : (a) Strain evaluation by Gram staining of the five selected strains (×1000), and (b) phylogenetic tree analysis based on 16S rRNA gene sequences of the five selected isolates.